Prospective Evaluation of Laparoscopic Pancreatic Biopsies in 11 Healthy Cats - Cosford, K. L.; Shmon, C. L.; Myers, S. L.; Taylor, S. M.; Carr, A. P.; Steiner, J. M.; Suchodolski, J. S.; Mantovani, F. [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
BackgroundDefinitive diagnosis of feline pancreatic disease is dependent on histologic examination of biopsies.HypothesisLaparoscopic punch biopsy of the pancreas does not significantly affect pancreatic health or clinical status of healthy cats, and provides an adequate biopsy sample for histopathology.AnimalsEleven healthy female domestic shorthair cats.MethodsEffects of laparoscopic pancreatic visualization alone in 5 cats compared with laparoscopic pancreatic visualization and punch biopsy in 6 cats were studied. Temperature, pulse, and respiratory rate, physical examination, and daily caloric intake were evaluated for 1 week before and 1 week after the procedure. Pain scores (simple descriptive score and dynamic interactive visual assessment score) were evaluated hourly during the 1st 6 hours postprocedure. Complete blood cell counts, serum biochemical profiles, serum feline pancreatic lipase immunoreactivity, and urine specific gravity were evaluated before the procedure and at 6, 24, and 72 hours postprocedure. One month postprocedure, during sterilization, the pancreas was reassessed visually in all cats, and microscopically in the biopsy group.ResultsFor all variables evaluated, there were no significant differences between biopsy and control cats. Re-evaluation of the pancreatic biopsy site 1 month later documented a normal tissue response to biopsy. The laparoscopic punch biopsy forceps provided high-quality pancreatic biopsy samples with an average size of 5 mm x 4 mm on 2-dimensional cut section.Conclusions and Clinical ImportanceLaparoscopic pancreatic biopsy is a useful and safe technique in healthy cats.
Keywords: Feline; Laparoscopy; Pancreas